Gibbon Refuge at Sunset Zoo: a conservation based exhibit design for species preservation - Morrow, Sarah (Kansas State University, 2009)
The primary reasons for the existence of contemporary zoological parks are presented as conservation and conservation education. But in reality, human entertainment is the primary function of traditional zoos. There is a moral dilemma behind the practice of removing wild animals from their native habitats and holding them captive, primarily for the purpose of human entertainment and education. Exhibits designed with these human desires in mind never completely meet the needs of the animal. An exhibit designed with conservation in mind can fully address animal needs. The moral dilemma of keeping wild animals captive can be reconciled if the purpose of conservation shifts to the forefront of exhibit design. The term conservation, in this setting, refers to a habitat where a healthy, captive population can be sustained. Conservation means acquiring an in-depth understanding of an animal species and combining it with thoughtful, insightful design that responds to the species’ needs first. Secondary design considerations include facilitating the work of the animal keeper and visitor education and recreation. The keeper plays an important role in the health and well-being of the animal; a functional workplace is essential to the keeper’s job. The visitor plays an essential role in maintaining the funding that supports the zoo. In order for zoos to maintain adequate funding, they need visitors. To make this experience mutually worthwhile, exhibit design must create an experience that visitors want to be a part of, and the exhibit should impart an educational message to these visitors. This conservation-minded approach results in an exhibit that will serve primarily as a conservation facility. The exhibit is better suited to the animal by encouraging natural behavior and more accurately recreating natural habitat. A conservation exhibit can also fulfill the secondary purpose of human education by providing the visitor with a much richer depiction of the animal in its natural state, as well as showing visitors the need for species conservation.
Keywords: Exhibit design; Zoological park; Gibbon; Landscape Architecture (0390)